Realization of the Evristic Combination Methods by Means of Computer Graphics - S. A. Novoselov; N. P. Ivanova (Russian State Vocational Pedagogical University, 2015)
The paper looks at the ways of enhancing and stimulating the creative activity and initiative of pedagogic students - the prospective specialists called for educating and upbringing socially and professionally competent, originally thinking, versatile personalities. For developing their creative abilities the author recommends introducing the heuristic combination methods, applied for engineering creativity facilitation; associative-synectic technology; and computer graphics tools. The paper contains the comparative analysis of the main heuristic method operations and the computer graphics redactor in creating a visual composition. The examples of implementing the heuristic combination methods are described along with the extracts of the laboratory classes designed for creativity and its motivation developments. The approbation of the given method in the several universities confirms the prospects of enhancing the students' learning and creative activities.